2012
DOI: 10.1111/j.1708-8208.2012.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implants in Patients with Oral Lichen Planus: A Cross‐Sectional Study

Abstract: The results of the present study suggest that implants do not influence manifestations of OLP. OLP is not a risk factor for peri-implantitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 26 publications
4
62
2
Order By: Relevance
“…The results indicated that the presence of OLP was not associated with a higher prevalence of peri‐implant mucositis . These results were confirmed in a cross‐sectional study failing to report significant differences in the prevalence of peri‐implant mucositis in patients with dental implants and diagnosed with or without OLP . However, in patients diagnosed with OLP and gingival desquamation, a significantly higher prevalence of peri‐implant mucositis was observed .…”
Section: Similarities and Differences Between Risk Indicators/factorssupporting
confidence: 54%
“…The results indicated that the presence of OLP was not associated with a higher prevalence of peri‐implant mucositis . These results were confirmed in a cross‐sectional study failing to report significant differences in the prevalence of peri‐implant mucositis in patients with dental implants and diagnosed with or without OLP . However, in patients diagnosed with OLP and gingival desquamation, a significantly higher prevalence of peri‐implant mucositis was observed .…”
Section: Similarities and Differences Between Risk Indicators/factorssupporting
confidence: 54%
“…In total 16 prospective studies [14,18,19,28,35-40,44,45,47,48,50,53] from which 5 were controlled clinical trials [38-40,44,48] and 1 cross-sectional study [45], 23 retrospective studies [15-17,20,23-27,29-34,41-43,46,49,51,52,54] and two case series studies [21,22] were included in present research.…”
Section: Resultsmentioning
confidence: 99%
“…Implant survival and success rate was 100% vs. 96.8% in the control group [44]. Two studies confirmed that implant placement didn’t influence OLP manifestation [45,46]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were single case reports or case series. Three controlled studies – one prospective the others retrospective – were found.…”
Section: Resultsmentioning
confidence: 99%